Monoclonal antibodies recognizing the surface autolysin IspC of Listeria monocytogenes serotype 4b: epitope localization, kinetic characterization, and cross-reaction studies. - Jennifer Ronholm; Henk van Faassen; Roger MacKenzie; Zhiyi Zhang; Xudong Cao; Min Lin (PLoS ONE, 2013)
Listeria monocytogenes serotype 4b is responsible for a high percentage of fatal cases of food-borne infection. In a previous study, we created 15 monoclonal antibodies (MAbs) against a ≈ 77 kDa antigen that is associated with the cell surface of live L. monocytogenes serotype 4b cells. Here we report an extensive characterization of these MAbs to further their development as diagnostic reagents. The ≈ 77 kDa target antigen was identified by mass spectrometry and N-terminal sequencing to be IspC, a novel surface associated autolysin. Epitope localization experiments revealed that each of the 15 MAbs recognized the C-terminal cell-wall binding domain of IspC. The presence of IspC was shown to be highly conserved within L. monocytogenes serotype 4b, as evidenced by a strong reaction between anti-IspC MAbs and all 4b isolates. To determine the range of cross-reactivity with other L. monocytogenes serotypes ELISA was used to test each MAb against multiple isolates from each of the L. monocytogenes serotypes. Of the 15 MAbs, five: M2774, M2775, M2780, M2790 and M2797, showed specificity for L. monocytogenes serotype 4b and only cross reacted with serotype 4ab isolates. The kinetics of the interaction between each of the MAbs and IspC was measured using surface plasmon resonance. The MAbs M2773, M2792, M2775, M2797 and M2781 each had very low dissociation constants (4.5 × 10(-9) to 1.2 × 10(-8) M). While several of these antibodies have properties which could be useful in diagnostic tests, the combined high fidelity and affinity of M2775 for the IspC protein and serotype 4b isolates, makes it a particularly promising candidate for use in the development of a specific L. monocytogenes serotype 4b diagnostic test.